An evaluation of purchasing department strategies in handling food and beverage operations in five-star hospitality settings - Pratiwi, Ni Putu Eka; Utami, Made Ayu Jayanti Prita; Wajdi, Majid; Chaurasiya, Sneha (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2025)
This study aims to analyse the handling and procurement of food and beverage (F&B) products by the Purchasing Department at The Westin Resort Nusa. As a core operational area in the hospitality industry, efficient F&B management significantly influences guest satisfaction and operational costs. The objective of this research is to assess how the purchasing department manages supplier selection, procurement processes, stock monitoring, and coordination with the kitchen and F&B service teams to ensure product availability, quality, and cost-efficiency. The study employs a qualitative descriptive method, using interviews, observations, and documentation as primary data collection techniques. Interviews were conducted with key purchasing staff and F&B personnel to understand workflows, procurement standards, and challenges faced. Observations of daily procurement activities and stock handling were also carried out, along with document reviews including purchase orders, vendor records, and inventory reports. The analysis reveals that the purchasing department plays a pivotal role in maintaining the consistency of raw material quality while balancing cost-effectiveness. Key strengths include a well-established supplier network, digitalized procurement records, and adherence to hotel SOPs. However, challenges were found in managing fluctuating supply prices, occasional delays in delivery, and the need for stronger interdepartmental communication. The study concludes that while the purchasing system is generally effective, it requires continuous monitoring, vendor performance reviews, and integration with inventory systems to enhance real-time responsiveness. These improvements are crucial for sustaining high service standards in the resort’s F&B operations.